Cameron Highlands Issues And Challenges In Sustainable Development [HC79.E5 C182 2006 f]. - Chan , Ngai Weng (School of Humanities, Universiti Sains Malaysia, 2006)

(untitled)
Cameron Highlands is one of Malaysia's most popular hill stations. It is well known for its cool weather, hill cottages and tea plantations. The purpose of this chapter is to draw attention to the various forests types within Cameron Highlands with its special significance for biological diversity and important water resources. The climate of Cameron Highlands is discussed in light with the various threats and challenges that this habitat faces and also considering the limited degree of protection afforded to this unique hill station.